P46 Improving the quality of preferred plan of care discussion using a companion guide for patients with advanced dementia. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Ho, E
Abstract : Background: For patients with advanced dementia, preferred plan of care conversations helps to improve end of life outcomes by creating an opportunity for their carers to discuss about the circumstances in which they would prefer to limit life prolonging treatments and instead opt for an approach that prioritizes quality of life. A discussion aid provides patients and families with structured information about clinical choices and help enhance the clinical decision making. This will improve time efficiency and quality of informed decision making by increasing disease specific knowledge, reducing decisional conflict and promote evidence-based treatments. Objectives: Use of a discussion guide to improve the quality of discussion for patients with advanced dementia. Methodology: This study was a cross sectional study conducted in August 2018. The target population are physicians in the department of Geriatric Medicine, Tan Tock Seng Hospital. A discussion aid was designed to present balances, evidence-based information about risk, benefits and alternatives of clinical decisions to aid in discussion of end of life care in patients with advanced dementia. Results: Of the 43 physicians surveyed, 30% of them strongly agreed; 62% agreed; 4% Neither agree nor disagree and 2% disagree that the discussion aid will improve quality of ACP discussions. Conclusion: Most of the physicians surveyed felt that the discussion guide will improve the quality of communication and ACP discussion in patients with advanced dementia. They are also likely to use this guide for future ACP discussions.